The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jclepro.2019.117690
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria efficiency assessment of international biomass supply chain pathways using Data Envelopment Analysis

Abstract: Most European countries have committed to ambitious emissions reduction goals. Energy generation in particular is responsible for more than 30% of global emissions, where significant focus has been placed on renewable energy generation, including biomass. On the one hand, there are countries, like the UK, where the biomass stock is insufficient to meet the demand; on the other hand, there are countries, like Brazil, where the stock significantly exceeds the demand. To promote a natural symbiosis, it is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Rentizelas et al [63] stressed the need for a decision support tool to facilitate the supply chain design rather than assessing the supply chain of specific origin and destination location. A multicriteria tool based on data envelopment analysis which considers the environmental impact and cost is The review by Diesenreiter and Kranzl [57] suggested that no customised models are available for incorporating global import/export potentials and international trade.…”
Section: Methods Used In Biofuel Downstream Supply Chain Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Rentizelas et al [63] stressed the need for a decision support tool to facilitate the supply chain design rather than assessing the supply chain of specific origin and destination location. A multicriteria tool based on data envelopment analysis which considers the environmental impact and cost is The review by Diesenreiter and Kranzl [57] suggested that no customised models are available for incorporating global import/export potentials and international trade.…”
Section: Methods Used In Biofuel Downstream Supply Chain Planningmentioning
confidence: 99%
“…Rentizelas et al [63] stressed the need for a decision support tool to facilitate the supply chain design rather than assessing the supply chain of specific origin and destination location. A multicriteria tool based on data envelopment analysis which considers the environmental impact and cost is conducted to identify the efficiency of alternative pathways (Up to 56 pathways between Brazil and the UK) of international biomass supply chains are developed.…”
Section: Methods Used In Biofuel Downstream Supply Chain Planningmentioning
confidence: 99%
“…For example, the "preservation of the soil productivity" [25,26], as an environmental enabler, is affected by environmental potentials, needs and changes, and affects the forest management efficiency and the quantity and quality of utilization. The "optimal investments in importing and exporting capabilities" [27], as economic enabler, are affected by the decisions on a micro and macro scale, and affect the extension and productivity of forest biomass and bioenergy SCN. Furthermore, the "improvement of public awareness and perceptions levels" [28,29], as a social enabler, is affected by training and the revelation of advantages and disadvantages to the public, and affects the acceptance and development rates of these industries.…”
Section: Enablers Of Forest Biomass and Bioenergy Supply Chain Resiliencementioning
confidence: 99%
“…In the south of Brazil, the sugar cane industry has an important impact on the economy, and the rail transportation service available is essential to assist in both improving the performance of this sector and decreasing the respective costs. Other authors [3,[29][30][31] investigated the efficiency of rail operations in Brazil, mostly regarding environmental factors, but without developing approaches to understanding the changes that occurred due to interventions, such as mergers between different companies.…”
Section: Rail Productionmentioning
confidence: 99%
“…Although there is substantial literature on rail economics, production costs and analysis of rail productivity, research work on rail production analysis using econometric approaches and efficiency analysis are not extensive in Brazil. According to the best of our knowledge, only six studies have been identified touching upon this topic [3,[29][30][31]45,46], where two of them [45,46] were solely presented in national conferences.…”
Section: Cowie and Riddington (1996)mentioning
confidence: 99%